Perancangan Aplikasi Kriptografi Menggunakan Algoritma RC4 (Rivest Code 4) Untuk Mengamankan Pesan Email di PT CREATIFACTORY - Rifki Darmawan; Sewaka (CV. Multi Kreasi Media, 2023)
The development of information technology that is so advanced rapidly has made information a basic need for everyone who has it. To be able to secure the information we have, one of the techniques for securing data and information is to use cryptography. Therefore, the author makes an application that can maintain the confidentiality of information from data theft crimes, and the application in question is a web-based email cryptography application. This application can be used to secure the data contained in the user's email. In this application the cryptographic algorithm that will be used is the Rivest Code 4 (RC4) algorithm. RC4 is a stream cipher type algorithm that processes input data units. The Rivest Code 4 (RC4) algorithm is also part of a symmetric algorithm, where the encryption and decryption processes have the same key. Making this application using the PHP programming language. The modeling method in making this application is the UML (Unified Modeling Language) method. The result of this research is an email security cryptography application that is able to encrypt and decrypt documents in formats such as *ai, *ps, *indd, *docs, *xls, *pdf, *ppt, *svg etc, using the Rivest Code 4 (RC 4) algorithm web based.